2009
DOI: 10.1007/s11606-009-1032-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pre-Clinical Clinical Skills Curriculum on Student Performance in Third-Year Clerkships

Abstract: BACKGROUND:Research on the outcomes of preclinical curricula for clinical skills development is needed to assess their influence on medical student performance in clerkships.OBJECTIVE: To better understand the impact of a clinical-skills curriculum in the pre-clinical setting on student performance. DESIGN:We conducted a non-randomized, retrospective, pre-post review of student performance evaluations from 3rd-year clerkships, before and after implementation of a clinical-skills curriculum, the Colleges (2001C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 35 publications
(31 reference statements)
0
39
0
Order By: Relevance
“…Methods used for feedback and grading are discussed in the text Learning such clinical skills early in the medical education curriculum has many positive documented effects. Jackson et al [7] found that the "implementation of a pre-clinical fundamental skills curriculum appears to be associated with improved clerkship performance during the third year of medical school while Durand et al [8] noted that "a student's ability to organize differential diagnoses was directly correlated with spending less on diagnostic testing when asked to order tests as part of a clerkship experience." They [8] further state that "given the current climate of cost consciousness in medicine, it makes sense to prepare students to be organized in their approach to the formation of the differential diagnosis" to which the authors would agree, especially given the concerns many now express regarding the ever-rising costs associated with unnecessary testing in many healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…Methods used for feedback and grading are discussed in the text Learning such clinical skills early in the medical education curriculum has many positive documented effects. Jackson et al [7] found that the "implementation of a pre-clinical fundamental skills curriculum appears to be associated with improved clerkship performance during the third year of medical school while Durand et al [8] noted that "a student's ability to organize differential diagnoses was directly correlated with spending less on diagnostic testing when asked to order tests as part of a clerkship experience." They [8] further state that "given the current climate of cost consciousness in medicine, it makes sense to prepare students to be organized in their approach to the formation of the differential diagnosis" to which the authors would agree, especially given the concerns many now express regarding the ever-rising costs associated with unnecessary testing in many healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…Taiwan's medical training consists of 7 years of post-secondary medical school followed by Effects of a new parallel primary healthcare centre and on-campus training programme on history taking, physical examination skills and medical students' preparedness: a prospective comparative study in Taiwan Ying-Ying Yang, 1,2,3 Shuu-Jiun Wang, 1,4 Ling-Yu Yang, 1,5 Jiing-Feng Lirng, 1,4 Chia-Chang Huang, 1,2 Jen-Feng Liang, 1,5 Fa-Yauh Lee, 1,3,4 Shinn-Jang Hwang, 1,4 Chin-Chou Huang, 1 â–º Similar preparation period before assessments, as well as randomised raters, simulation patients, students and standardised processes in group objective structured clinical examination (GOSCE)/ OSCE ensured the comparability of the results of the primary healthcare centre (PHCC) group and the PHCC training in combination with on-campus history taking (HT) and physical examination (PE) training (PHCC+on-campus) group. â–º Pre-clerks in both modules, which equally extended the whole fourth year of medical education, were volunteers that were more committed, brighter and motivated; this may have resulted in some degree of selective bias.…”
Section: Introductionmentioning
confidence: 99%
“…Several institutions have conducted pre-and post-LC implementation analyses that associated LCs with positive outcomes including students' increased comfort in clinical skills, 7 Clinical Performance Examination scores, 8 and performance on clinical rotations, 9 as well as connections between students, involvement in leadership and service activities, student access to faculty, and positive perceptions of the learning environment (LE). 10 The American Medical Association (AMA)-sponsored Learning Environment Study (LES) 11 includes two institutions that have published descriptions of their LCs: University of Arizona College of Medicine-Tucson 12 and Stanford University School of Medicine.…”
mentioning
confidence: 99%